Climate extreme variables generated using monthly time‐series data improve predicted distributions of plant species. Issue 4 (2nd February 2021) - Stewart, S. B.; Elith, J.; Fedrigo, M.; Kasel, S.; Roxburgh, S. H.; Bennett, L. T.; Chick, M.; Fairman, T.; Leonard, S.; Kohout, M.; Cripps, J. K.; Durkin, L.; et al.
Abstract : Extreme weather can have significant impacts on plant species demography; however, most studies have focused on responses to a single or small number of extreme events. Long‐term patterns in climate extremes, and how they have shaped contemporary distributions, have rarely been considered or tested. BIOCLIM variables that are commonly used in correlative species distribution modelling studies cannot be used to quantify climate extremes, as they are generated using long‐term averages and therefore do not describe year‐to‐year, temporal variability. We evaluated the response of 37 plant species to base climate (long‐term means, equivalent to BIOCLIM variables), variability (standard deviations) and extremes of varying return intervals (defined using quantiles) based on historical observations. These variables were generated using fine‐grain (approx. 250 m), time‐series temperature and precipitation data for the hottest, coldest and driest months over 39 years. Extremes provided significant additive improvements in model performance compared to base climate alone and were more consistent than variability across all species. Models that included extremes frequently showed notably different mapped predictions relative to those using base climate alone, despite often small differences in statistical performance as measured as a summary across sites. These differences in spatial patterns were most pronounced at the predicted range margins, and reflect the influence of coastal proximity, continentality, topography and orographic barriers on climate extremes. Species occupying hotter and drier locations that are exposed to severe maximum temperature extremes were associated with better predictive performance when modelled using extremes. Understanding how plant species have historically responded to climate extremes may provide valuable insights into our understanding of contemporary distributions and help to make more accurate predictions under a changing climate.